1999
DOI: 10.1063/1.124187
|View full text |Cite
|
Sign up to set email alerts
|

Light emission during fracture of a Zr–Ti–Ni–Cu–Be bulk metallic glass

Abstract: A light emission phenomenon observed during dynamic fracture of a bulk metallic glass, Zr 41.2 Ti 13.8 Cu 12.5 Ni 10 Be 22.5 ͑at. %͒, has been investigated using Charpy V-notch impact specimens. Unlike more conventional crystalline metals, these Zr-based amorphous alloys emit intense flashes of visible light when ruptured. The mechanisms for this surprising behavior are unknown and the phenomenon remains uncharacterized. Here we report spectroscopic measurements of the light emitted from specimens fractured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(42 citation statements)
references
References 15 publications
2
40
0
Order By: Relevance
“…Evidence of ∼500 K rise after fracture was observed, 18 along with a rise of over ∼1000 K detected during impact fracture under nitrogen environment (to avoid oxidation). 34 The more recent experimental results of Lewandowski and Greer clearly demonstrate that temperature rise in the shear bands can be as high as a few thousand Kelvin over a few nanoseconds. 35 In the present, experiments features that appear to be resolidified droplets suggest that localized melting may have occurred during the final failure even under quasi-static tests [see Fig.…”
Section: A Mechanical Propertiesmentioning
confidence: 96%
“…Evidence of ∼500 K rise after fracture was observed, 18 along with a rise of over ∼1000 K detected during impact fracture under nitrogen environment (to avoid oxidation). 34 The more recent experimental results of Lewandowski and Greer clearly demonstrate that temperature rise in the shear bands can be as high as a few thousand Kelvin over a few nanoseconds. 35 In the present, experiments features that appear to be resolidified droplets suggest that localized melting may have occurred during the final failure even under quasi-static tests [see Fig.…”
Section: A Mechanical Propertiesmentioning
confidence: 96%
“…Infrared surface measurements by Flores and Dauskardt [39] indicate a peak temperature increase of H55 K due to the plastic deformation at the crack tip. Gilbert et al [18] observed that the Zr 41.2 Ti 13.8 Cu 12.5 Ni 10 Be 22.5 glass fractured with emission of bright sparks upon impact testing in air whereas no sparks were seen when tested in nitrogen atmosphere. They argued that along with oxidation induced heat generation, intense heat was also generated due to plastic work.…”
Section: Fracture Mechanismsmentioning
confidence: 99%
“…19,50) Temperature increase and a possible drop in the viscosity within shear bands before fracture are still hotly debated. [36][37][38]51,52) However, a significant temperature increase at the moment of fracture leading to viscous flow features on the fracture surfaces seems to be generally accepted. Observations such as deformation-induced nanocrystallization, 9,10,12,53) and voids and vacancy cluster formations [54][55][56] find explanations in temperature rises (adiabatic heating) but may also be interpreted as an effect of dilatation and generation of free volume.…”
Section: Discussionmentioning
confidence: 99%